Analysis of Dermatologic Consultations in a Neonatal Intensive Care Unit Over a 7‐Year Period: Retrospective Review of 60 Cases. Issue 5 (September 2017) - Kang, Jeong Nan; Kim, Do Hyeong; Park, So Hee; Seol, Jung Eun; Kim, Hyojin
Abstract: Background/Objectives: The need for dermatology consultations for neonatal intensive care unit (NICU) patients is increasing, but no study has systemically examined the skin diseases of patients in NICUs. The aim of this study was to analyze dermatology consultations in the NICU of a tertiary medical center in Korea and determine the effect of the dermatology consultation on the clinical course and management of the patients after the consultation. Methods: The medical records of patients undergoing dermatologic consultation during their stay in a NICU between March 2009 and February 2016 were reviewed retrospectively. Results: Sixty patients were enrolled in this study; the male‐to‐female ratio was 1:1.1, and mean age at the time of consultation was 3.7 weeks. Mean gestational age was 33.7 weeks, and 35 of the subjects (58.3%) were preterm neonates. Mean birth weight was 2.14 kg (range 550–4, 200 g). The most‐common disease category was birthmarks and neoplasms (20.0%), followed by eczematous dermatoses (18.3%), skin appendageal disease (16.7%), and infectious disease (13.3%). Conclusion: This study identified the dermatologic problems of neonates in a NICU and can raise dermatologists' awareness of the types of patients they may encounter in a NICU.